Thyroid Response to Mercury: Varied Effects on Function and Structure - A Review of the Latest Research - Kubicka-Figiel, Martyna; Martyka, Anna; Taborska, Nina (Journal of Education, Health and Sport, 2024)
Introduction In the current era of burgeoning industry, our exposure to various detrimental environmental factors, including mercury, has become increasingly prevalent. Recognized by the World Health Organization (WHO) as one of the most significant threats to public health, mercury induces a multitude of harmful effects on the entire body. Our focus in this article will be directed towards examining the specific impact of mercury on the thyroid. Purpose of the study The purpose of the study was to review the latest literature on the effects of mercury on the thyroid gland. Materials and Methodology Literature selections of medical databases PubMed and Google Scholar from the last six years (2017-2023) were performed. Articles were searched in English using the following key words: mercury, thyroid. Results Research consistently confirms mercury accumulation in thyroid cells, increasing with age. Mercury exposure influences thyroid function, raising the risk of hormonal issues and potential thyroid cancer. It also interacts with other elements, compounding adverse effects on the thyroid. Conclusion Presently, there is a limited number of studies specifically addressing the effects of mercury on the human thyroid gland. Consequently, it is probable that the full spectrum of its impacts on the thyroid has not yet been thoroughly investigated. Further research is imperative to delve into this subject comprehensively. Additionally, there is an urgent call for initiatives aimed at enhancing public awareness regarding the sources of mercury in the environment and food, along with strategies to mitigate exposure to this harmful substance.